Distinct mechanisms for TMPRSS2 expression explain organ-specific inhibition of SARS-CoV-2 infection by enzalutamide - Fei Li (Nature Portfolio, 2021)
Enzalutamide, an approved drug for prostate cancer, acts on TMPRSS2 expression, a key mediator for SARS-CoV-2 infection. Here, the authors characterize the anti-SARS-CoV-2 effects of Enzalutamide in prostate cancer cells, lung cancer cells, human lung organoids and in hACE2-transduced Tmprss2 knockout mice and show lack antiviral action in human lung cells and human lung organoids, likely due to the AR-independent TMPRSS2 expression in mouse and human lung epithelial cells.